Benchmarking care outcomes for young adults with type 1 diabetes in Australia after transition to adult care. Issue 4 (9th September 2021) - Rueter, Phidias; Farrell, Kaye; Phelan, Helen; Colman, Peter; Craig, Maria E.; Gunton, Jenny; Holmes‐Walker, D. Jane; ,
Abstract: Aim: To determine advantages conferred by a youth‐specific transition clinic model for young adults with type 1 diabetes (T1D) at Westmead Hospital (WH) as compared with Australian registry data. Methods: Prospectively collected data included age, diabetes duration, visit frequency, post code, BMI, mode of insulin delivery, continuous glucose monitoring, HbA1c, albumin creatinine ratio, BP, retinopathy and diabetic ketoacidosis (DKA) for all WH T1D clinic attendees aged 16–25 between January 2017 and June 2018 ( n  = 269). Results were compared with data collected during the same time period from 2 separate Australian data registries, one longitudinal (Australasian Diabetes Data Network, ADDN) and one a spot survey (the Australian National Diabetes Audit, ANDA). Results: Across the three cohorts, HbA1c was similar (respectively, WH, ADDN, ANDA; 8.7%[72mmol/mol], 8.7%[72mmol/mol], 8.5%[69mmol/mol]) and HbA1c was significantly higher in young adults <21 years (8.7–8.9%[73‐75mmol/mol]) as compared with ≥21 years (8.5%[69mmol/mol], p  < .002). In the WH cohort, median interval between visits was shorter than in ADDN (4.5 vs. 9.0 months) and DKA was lower (respectively, 3.6 and 9.2/100 patient years; p  < .001). Conclusions: While suboptimal HbA1c was recorded in all centres, the WH model of care saw increased attendance and reduced admissions with DKA as compared with other Australian adult centres. Abstract : A model of care for young people with type I diabetes as they transition to adult care was benchmarked with two separate Australian data registries. Similar glycaemic outcomes were achieved nationally but the care model achieved a marked reduction in diabetic ketoacidosis and increased clinic attendance frequency.